Income Distribution and Tax and Government Social Spending Policies in Developing Countries - Chu, Ke-young (IMF Working Papers; Working Paper ;, 2000)
This paper reviews income distribution in developing (and transition) countries in recent decades. On average, before-tax income distribution in developing countries is less unequal than in industrial countries. However, unlike industrial countries, developing countries in general have not been able to use tax and transfer policies effectively to reduce income inequality. During the 1980s and 1990s, many developing countries experienced an increase in income inequality. The government health care and primary and secondary education programs in developing countries are not well targeted, but their incidence tends to be progressive.